Kebijakan Pemerintah Dalam Menaikkan Harga Bahan Bakar Minyak Serta Dampaknya Bagi Masyarakat - Zahra Silbaqolbina, Yumna; Ulfatun Najicha, Fatma (Jurnal Syntax Fusion, 2022)
The increase in the price of fuel oil, especially Pertamax, which was officially announced on April 1, 2022, raised various questions in the community. However, behind all the questions regarding the reason for the government to increase the price of fuel oil, the government has considered the decision carefully so that the policy that has been taken cannot be misdirected or detrimental to the community. By using the literature method, the author finds that the government's decision to consider the increasingly scarce oil resources and the needs of the community must also be met, so the policy of making Pertalite a subsidized fuel and increasing the price of Pertamax is correct.